2021
DOI: 10.1007/s12208-021-00289-0
|View full text |Cite
|
Sign up to set email alerts
|

Message framing, non-conscious perception and effectiveness in non-profit advertising. Contribution by neuromarketing research

Abstract: Advertising for non-profit organizations through television commercials is a valuable means of communication to raise awareness and receive donations. When it comes to social aspects, personal attitudes such as empathy are significant for reinforcing the intention to donate; and the study of eliciting emotions has critical attention in the literature, especially some types of emotion, such as guilt which mediates empathy. Different methodologies have been used to measure consumer emotions when faced with TV ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 72 publications
0
20
0
1
Order By: Relevance
“…Due to cost and time considerations, mainly for studies using several types of equipment, neuroscience studies typically deal with low sample sizes and are not intended to be representative (Button et al , 2013; Martinez-Levy et al , 2021; Muñoz-Leiva et al , 2019; Nord et al , 2017). The sample size of the present study was similar to what was practiced in similar neuroscience experimental studies (Esch et al , 2012; Gordon et al , 2018) and larger than most of the research studies pointed out in a review of eye-tracking studies presented by Scott et al (2019).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Due to cost and time considerations, mainly for studies using several types of equipment, neuroscience studies typically deal with low sample sizes and are not intended to be representative (Button et al , 2013; Martinez-Levy et al , 2021; Muñoz-Leiva et al , 2019; Nord et al , 2017). The sample size of the present study was similar to what was practiced in similar neuroscience experimental studies (Esch et al , 2012; Gordon et al , 2018) and larger than most of the research studies pointed out in a review of eye-tracking studies presented by Scott et al (2019).…”
Section: Methodsmentioning
confidence: 99%
“…In this context, it is seen that emotions can also impact visual attention to ads (Breuer et al , 2021; Martinez-Levy et al , 2021). Breuer et al (2021) indicate that viewers’ emotions during live broadcast games can influence visual attention to the sponsors’ messages exposed, and Martinez-Levy et al (2021) found that the induction of empathy through images showing the reality of war within the ads increases visual attention to nonprofit advertising and donations. However, no studies have been found that investigate the effect of emotion induction previous to the ads’ viewing on visual attention to them.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Partiendo de estas premisas, se ha realizado un gran número de investigaciones recurriendo a técnicas de neuromarketing para medir variables como la atención, el impacto emocional o el recuerdo de los mensajes publicitarios. A modo de ejemplo, en estudios sobre publicidad de servicio público, se ha investigado: la atención, recuerdo y emoción de los consumidores ante el visionado de publicidad social relacionada con la eficiencia energética (Gordon et al, 2018); la atención y la intención de donación en la publicidad benéfica no gubernamental (dos Santos et al, 2018); la relación entre la reacción cerebral de los sujetos ante mensajes publicitarios sobre homosexualidad y la actitud hacia el tema anunciado (Maison y Oleksy, 2017); el impacto del contexto social en las respuestas neurofisiológicas de los consumidores cuando se exponen a los mensajes publicitarios (Pozharliev et al, 2017); la relación entre las reacciones cognitivas y emocionales y la eficacia de mensajes publicitarios de asociaciones sin ánimo de lucro (Martínez-Levy et al, 2021); la respuesta emocional a los mensajes publicitarios contra el tabaco (Rath et al, 2019); el efecto de las percepciones de los destinatarios sobre la fuente del mensaje en audiovisuales sobre alcoholismo (Stanojlovic et al, 2020).…”
Section: Introductionunclassified